New World Orphanostigma Guenée, 1854, including a new species from Costa Rica (Lepidoptera: Crambidae: Spilomelinae) - Solis, M. Alma; Cock, Matthew J. W.; Janzen, Daniel; Hallwachs, Winnie (Zootaxa, 2024)
Orphanostigma haemorrhoidalis Guenée, 1854, was described from Brazil and introduced worldwide for the biological control of Lantana camara L. (Verbenaceae). Orphanostigma futilalis (Barnes & McDunnough, 1914), rev. stat., described from south Texas, United States, is removed from synonymy with O. haemorrhoidalis. We designate lectotypes for O. futilalis, new lectotype, and O. haemorrhoidalis, new lectotype, to stabilize the names of these species. We describe Orphanostigma eugeniephillipsia Solis, sp. nov., from Costa Rica and provide adult and genitalia images for all three New World species.